Application of Digital Images and Corresponding Image Retrieval Paradigm (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
We live in a world where digital images are constantly generated during our daily activities, whether private or business. They play an important role in our private life, showing important moments, people, places, or events and keeping their memory. Images are unavoidable in business, especially in digital marketing, web sales, social networks, medicine, security, and education. In general, images contribute to a better understanding of the message, increase the attractiveness of textual content, provide a better user experience, and can convey emotion quickly. The key advantage of the image is that very often, even a cursory glance at the image is enough to convey a message and arouse emotion and interest. But with the increase in digital image numbers, storage, organization, and retrieval problems arise. The paper describes the importance of images in different areas of application and different image retrieval paradigms that include text-based, content-based, and combined approaches. Also, the most popular image search tools and cloud storage services are compared and discussed. The conclusion comments on the applicability of existing approaches to image searches in different application domains and highlights the advantages and disadvantages of each of the approaches.